The Influence of Service Quality on The Interest of Consumer in Purchasing at Indomaret, Bandung - Karundeng, Meidy Lieke (Jurnal Ekonomis, 2024)
The purpose of this study is to test and provide empirical evidence regarding the effect of service quality on consumer purchasing interest at the Indomaret branch in Bandung. The background of this study is because service quality is one of the most important factors in determining consumer purchasing interest. The research method used is an empirical method with a descriptive and verification approach. Primary data were collected through questionnaires distributed to one hundred Indomaret customers. The findings indicate a notable relationship between service quality and consumer buying interest, suggesting that service quality plays a role in influencing consumer buying interest.